THE USE OF INFORMATION GAP TECHNIQUE TO IMPROVE SPEAKING SKILL - Ranti Harvi Rahimi (Universitas Islam Sultan Agung, 2016)
The final project was about the use of information gap technique to improve speaking skill. The objective of this study was to find out whether Information Gap technique was effective to improve students’ speaking skill or not. A quasi experimental research design was used in this study. The population of this study was the eleventh graders of MAN 2 Semarang in the academic year 2014/2015 with the number of population around 210 students. Non-equivalent groups’ pretest-posttest design was used in this study. Two classes were taken as the samples with around 60 students. The data were collected by using several activities. They were pre-test, treatment, and post-test. The result of this study shows that the pretest average of experimental class was 45.81 while the pretest average of control class was 42.12. After giving treatment for four meetings the posttest average of experimental class was 70.76 and while the posttest average control class was 49.48. The result of the analysis showed that there was a significant difference. It was supported by t-test result, the significant difference in the result of posttest between control and experimental class was 0.00 < 0.05. It means that the use of Information Gap technique in teaching speaking was better than the conventional method. It could be concluded that H1 was accepted that the use of Information Gap Technique was effective to improve students’ speaking skill